Dietary intake, body composition, and nutrition knowledge of Australian football and soccer players: Implications for sports nutrition professionals in practice - Devlin, B. L.; Leveritt, M. D.; Kingsley, M.; Belski, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Sports nutrition professionals aim to influence nutrition knowledge, dietary intake and body composition to improve athletic performance. Understanding the interrelationships between these factors and how they vary across sports has the potential to facilitate better-informed and targeted sports nutrition practice. This observational study assessed body composition (DXA), dietary intake (multiple-pass 24-hr recall) and nutrition knowledge (two previously validated tools) of elite and subelite male players involved in two team-based sports; Australian football (AF) and soccer. Differences in, and relationships between, nutrition knowledge, dietary intake and body composition between elite AF, subelite AF and elite soccer players were assessed. A total of 66 (23 +/- 4 years, 82.0 +/- 9.2 kg, 184.7 +/- 7.7 cm) players participated. Areas of weaknesses in nutrition knowledge are evident (57% mean score obtained) yet nutrition knowledge was not different between elite and subelite AF and soccer players (58%, 57% and 56%, respectively, p > .05). Dietary intake was not consistent with recommendations in some areas; carbohydrate intake was lower (4.6 +/- 1.5 g/kg/day, 4.5 +/- 1.2 g/kg/day and 2.9 +/- 1.1 g/kg/day for elite and subelite AF and elite soccer players, respectively) and protein intake was higher (3.4 +/- 1.1 g/kg/day, 2.1 +/- 0.7 g/kg/day and 1.9 +/- 0.5 g/kg/day for elite and subelite AF and elite soccer players, respectively) than recommendations. Nutrition knowledge was positively correlated with fat-free soft tissue mass (n = 66; r2 = .051, p = .039). This insight into known modifiable factors may assist sports nutrition professionals to be more specific and targeted in their approach to supporting players to achieve enhanced performance.